Attenuation of ultraviolet A‐induced alterations in NIH3T3 dermal fibroblasts by melatonin. (1st February 2014) - Rezzani, R.; Rodella, L.F.; Favero, G.; Damiani, G.; Paganelli, C.; Reiter, R.J.
Summary: Background: Sun exposure is responsible for long‐term clinical skin changes such as photoageing, photodamage and photocancers. Ultraviolet (UV)A wavelengths stimulate the production of reactive oxygen species (ROS) that may contribute to photoageing. To protect against oxidative stress, skin cells have developed several defence systems, including ROS and metal ion scavengers and a battery of detoxifying, haem‐degrading and repair enzymes. Melatonin's antioxidant activity is the result of three different but complementary actions: (i) a direct action due to its ability to act as a free radical scavenger; (ii) an indirect action that is a consequence of melatonin's ability to reduce free radical generation (radical avoidance); and (iii) its ability to upregulate antioxidant enzymes. Objectives: In this study, we focused our attention on the prevention of photodamage, choosing melatonin as an antioxidant agent. Methods: In the present study we analysed the effects of pretreatment of murine fibroblasts cells (NIH3T3) with melatonin (1 mmol L −1 ) followed by UVA irradiation (15 J cm −2 ). Thereafter, changes in components of the extracellular matrix and in some antioxidant enzymes (inducible and constitutive haem oxygenase) were evaluated. Results: We observed that UVA radiation caused altered expression of extracellular matrix proteins and induced the expression of inducible haem oxygenase. This increase was not sufficient to protect the cells from damage. Instead, melatonin pretreatment led to increased expression of haem‐degrading enzymes and suppression of UVA‐induced photodamage. Conclusions: These results suggest that melatonin, as a modifier of the dermatoendocrine system, may have utility in reducing the effects of skin ageing.